PERAN PESANTREN DALAM MENINGKATKANSIKAP ENTREPRENEURSHIP SANTRI MELALUI BIMBINGAN BERBASIS LIFE SKILL DI PONDOK PESANTREN AL-HIDAYAH KETEGAN - Makrifatul Ilmi Ilmi; M. Rochmanu Yahya (Fakultas Syariah IAI Al-Khoziny Buduran Sidoarjo, 2026)
Islamic boarding schools are one of the many educational institutions in Indonesia, so this institution participates in advancing human resources. Entrepreneurial ability is one of the things that must be intensified in Islamic boarding school educational institutions, the goal is so that students are not only able to apply religious knowledge but also be able to create jobs. This will make a great contribution to economic life, especially in creating entrepreneurs from the student environment, who have the characteristics of honesty, tenacity, independence and never give up. For this reason, this study focuses on the attitude of entrepreneurship of students through Life Skill guidance at Al-Hidayah Islamic Boarding School. This research is a type of descriptive qualitative research, namely research that uses field studies which are then described and explained through written data. Data collection techniques are carried out by means of interviews, observations and documentation. Meanwhile, the data analysis technique uses analytical descriptive techniques, namely describing the implementation of the entrepreneurial attitude of students through the guidance of Life Skills at the Al-Hidayah Islamic Boarding School. The results of the study show that the role of Islamic boarding schools in improving the entrepreneurial attitude of students through Life Skill guidance at Al-Hidayah Islamic Boarding School is in the form of various trainings and extracurricular activities that support the Entrepreneurship attitude process of Al-Hidayah Islamic Boarding School students. The training is bread sales, sewing skills training, Keychains, book shops, Rice paddies, Welding training. So, it can be concluded that Al-Hidayah Islamic Boarding School has had a positive impact on the attitude of entrepreneurship of students through